Pengaruh Lama Penjemuran terhadap Kualitas Mikrobiologis (Total BAL, Yeast, Antimikroba) dan pH pada Urutan Daging Ayam - Humaira, Nabila Ghassani; Suryaningsih, Lilis; Gumilar, Jajang (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Urutan is one of the traditional Balinese fermented products made from pork meat and fat processed traditionally in Bali. The utilization of pork in urutan able to be substituted with chicken meat, as chicken meat is highly preferred by the Indonesian population by considering it’s halal status and high consumption of broiler chicken meat. However, the optimal drying duration of urutan are still unknown. This study aimed to determine the effect of the duration of drying on the microbiological quality (total lactic acid bacteria, yeast antimicrobial) and pH of urutan products. This research was conducted using an experimental method using a completely randomized design (CRD) with 4 treatments and 5 repetitions consisting of P0 (D-0), P1 (D-2), P2 (D-4), and P3 (D-6). The research data were analyzed using variance followed by an orthogonal polynomial test. The results showed that the drying duration of urutan for 6 days showed a different total lactic acid bacteria by following the cubic regression pattern in the equation y = -0.055x3 + 0.4339x2 - 0.584x + 6.1144; different total yeast with a cubic regression pattern in the equation y = 0.0041x3 - 0.0457x2 + 0.2037x + 3.5355; different antimicrobial (Listeria monocytogenes) with a cubic regression pattern in the equation persamaan y = -0.0613x3 - 1.232x2 + 5.2273x + 11.264 and  (Salmonella thipymurium) y = 0.004x3 - 0.2288x2 + 0.2625x + 11.84; and a different pH by following the cubic regression pattern in the equation y = -0.0035x3 + 0.0632x2 - 0.4043x + 5.378. The optimal drying duration of urutan was up to the 4th day, which significantly affects the microbiological quality (total LAB, yeast¸antimicrobial) and pH.